Individual Knowledge Integration Through a Collaborative Integration Process in a High School Mathematics Class: Relation Between Gyration and Trigonometric Function - ODAGIRI, AYUMI (Kyōiku Shinrigaku Kenkyū, 2013)
The present study examined the mechanism of individual knowledge integration in the classroom through a collaborative integration process in which different ideas were integrated collectively, focusing in particular on the relation between knowledge of the subject matter and everyday knowledge. Eleventh graders (N=66) solved mathematical problems about the relation between gyration and trigonometric function in 3 stages: pre-test, during the lessons (2 conditions: a collaborative integration process or explanation of the answer by the teacher), and post-test. In the collaborative integration process, a problem that could be solved using various strategies was presented, and the students as a group structured the strategies with the help of the teacher. The results showed that in the collaborative integration process, the students’ knowledge was structured through a process in which, based on their understanding of the link between everyday knowledge and concrete knowledge of the subject matter, everyday knowledge and abstract knowledge about the subject were first linked, and then everyday knowledge and more detailed knowledge about the subject were linked. The post-test revealed that the students’ knowledge had been integrated.